70.5k views
1 vote
Help please I’m not good at rational functions.

Help please I’m not good at rational functions.-example-1
User Beetree
by
4.9k points

1 Answer

4 votes

Answer:

See below.

Explanation:


(6z^2-12z)/(4z^2-16z+16) +(3z)/(z^2-z-2) \\\\

First, factor the numerators and the denominators:


=(6z(z-2))/(4(z^2-4x+4))+(3z)/(z^2-z-2)\\=(6z(z-2))/(4(z-2)^2)+(3z)/((z-2)(z+1))\\=(3z)/(2(z-2))+(3z)/((z-2)(z+1))

Now, make the two denominators equivalent. To do this, we can multiply the first term by (z+1) and multiply the second term by 2. This will give us:


((z+1)/(z+1) )((3z)/(2(z-2)))+((2)/(2))((3z)/((z-2)(z+1)))\\=(3z(z+1))/(2(z-2)(z+1))+(6z)/(2(z-2)(z+1)) \\

Now, combine them since they have a common denominator:


=(3z^2+3z+6z)/(2(z-2)(z+1))\\ =(3z^2+9z)/(2(z-2)(z+1)) \\=(3z(z+3))/(2(z-2)(z+1))

This cannot be simplified further.

User Ted Collins
by
5.0k points